2017
DOI: 10.1016/j.autneu.2016.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the multifactorial nature of postoperative nausea and vomiting in women following surgery for breast cancer

Abstract: Background Postoperative nausea and vomiting (PONV) are two of the most frequent and distressing complications following surgical procedures, with as many as 80% of patients considered to be at risk. Despite recognition of well-established risk factors and the subsequent use of clinical guidelines, 20–30% of women do not respond to antiemetic protocols, indicating that there may be a genetic risk. Objective The purpose of this pilot study was to describe the incidence and explore the risk factors associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Disadvantages of PONV include the discomfort in the patient, prolonged length of hospital stay, and delays in recovery (Çekmen et al,2003). Besides these untoward consequences, severe PONV is associated with consequent fluid and electrolyte loss, aspiration into airways, contamination of the surgical site, increased strain in the sutured incision site, and increased intraocular and intraabdominal pressure (Kayhan Z ,2004;Wesmiller et al,2017).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Disadvantages of PONV include the discomfort in the patient, prolonged length of hospital stay, and delays in recovery (Çekmen et al,2003). Besides these untoward consequences, severe PONV is associated with consequent fluid and electrolyte loss, aspiration into airways, contamination of the surgical site, increased strain in the sutured incision site, and increased intraocular and intraabdominal pressure (Kayhan Z ,2004;Wesmiller et al,2017).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Genetic-association studies exploring the response to opioids after surgery reported not only on analgesic effects, but also on opioid-induced nausea and vomiting (OINV), 7 and on the response to 5-HT3 serotonin receptor antagonist anti-emetic drugs in the context of general inhalation anaesthesia. 8e14 In particular, the OPRM1 gene that encodes several mu-opioid receptor isoforms has been extensively studied in the context of OINV and PONV, 7,15e18 along with numerous SNPs of the 5-HT3A and 5-HT3B serotonin receptor genes (HTR3A and HTR3B), 19e21 the serotonin transport gene (SLC6A4), 22 the organic cation transporter-1 gene (OCT1), 23 the dopamine D2 receptor gene (DRD2), 24 the catechol-o-methyl-transferase gene (COMT), 25,26 the adenosine triphosphate-binding cassette subfamily B member 1 gene (ABCB1), 27 the TACR1 gene that encodes NK1 receptors, 28 and the CYP2D6 isoform of the cytochrome P450 superfamily. 29 This list might not even be exhaustive, and in addition, the response to 5-HT3 serotonin receptor antagonist anti-emetic drugs (e.g.…”
Section: G/g ( N=82) G/a ( N=88)mentioning
confidence: 99%
“…The four risk factors included in the Apfel Risk Score are female sex, prior history of motion sickness, or PONV, nonsmoking, and the use of postoperative opioids (2). In addition, elevated levels of distress may increase the severity of PONV (3,4) in the postoperative period. Concerns about changes in appearance and scarring, anesthesia, surgical procedures, diagnosis, and prognosis determine such distress.…”
Section: ' Introductionmentioning
confidence: 99%